CHANGING COSMETIC BRANDS INCREASE RISK OF FREQUENCY AND DEGREE OF ACNE VULGARIS IN FEMALE UNDERGRADUATE STUDENTS - Maharani, Annida; Pratiwi, Witri; Nauphar, Donny (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Acne vulgaris is a skin disease caused by chronic inflammation of the follicular pilosebacea marked by the presence of blackheads, papules, pustules, nodules, and cysts in place of healthy skin. One of the risk factors for Acne vulgaris is changing cosmetic brands which may contain comedogenic and acnegenic ingredients. The aim of this study is to find out the relationship of changing cosmetic brands and the prevalence of Acne vulgaris in female undergraduates. Methods: This was an observational study with cross sectional design. The subjects were 344 female undergraduates who used two out of four types of cosmetics, recruited by total sampling. Data were analyzed to see the relationship of changing cosmetic brands with the degree and the frequency of acne. Results: Based on Spearman correlation test, changing cosmetic brands has a strong positive correlation (r2= 0.762) with the degree of acne and a mild positive correlation (r2=0.461) with acne frequency. Chi-square test showed statistical significance (p<0.05) between changing cosmetic brands and the degree and frequency of acne. Subjects who frequently changes cosmetics has a 66 times higher risk of having bad acne (PR= 66.994; CI 95% = 32.099â139.320) and 8 times higher risk of having more frequent acne (PR= 8.432; CI 95% = 4.969-14.308) compared to subjects that do not frequently change cosmetics. Conclusion: Changing cosmetic brands increased the risk for both the degree of acne and the frequency of acne.Â